2021
DOI: 10.1177/00027642211013387
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Gender, and Age Dynamics in Michigan’s Urban and Rural Farmers Markets: Reducing Food Insecurity, and the Impacts of a Pandemic

Abstract: In recent decades, the number of farmer’s markets has increased dramatically across the country. Though farmers markets have been described as White spaces, they can play important roles in reducing food insecurity. This is particularly true in Michigan where farmer’s markets were crucial collaborators in pioneering programs such as Double-Up Food Bucks that help low-income residents and people of color gain access to fresh, healthy, locally grown food. This article examines the questions: (1) What are the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Full details of the study designs, settings, populations, and domains of food security examined are summarized in Table 2 . More than half of the 22 included studies were conducted in rural USA ( n = 13) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], with others being conducted in Australia [ 39 , 40 ], Canada [ 41 ], the UK [ 42 ], Poland [ 43 ], Israel [ 44 ], Chile [ 45 ] and Germany [ 46 ]. One study was conducted in an international sample, comprising participants from 62 different countries [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full details of the study designs, settings, populations, and domains of food security examined are summarized in Table 2 . More than half of the 22 included studies were conducted in rural USA ( n = 13) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], with others being conducted in Australia [ 39 , 40 ], Canada [ 41 ], the UK [ 42 ], Poland [ 43 ], Israel [ 44 ], Chile [ 45 ] and Germany [ 46 ]. One study was conducted in an international sample, comprising participants from 62 different countries [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n = 16) collected data on adult populations or household-level information [ 27 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 ], while two specifically focused on households or families comprising both adults and children [ 26 , 32 ]. Three studies reported on the impact of COVID-19 on food outlets such as stores [ 28 ], farmers markets [ 33 ], and food banks [ 46 ]. Sixteen were quantitative in design [ 26 , 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 , 41 , 43 , 44 , 45 , 46 , 47 ], with a sample size for the rural sample ranging from 50 to 1766 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations